Аўыл хожалығының баслы зыянкеси - жалпақ тисли крыса (nesokiya indica gray) менен гүрес усыллары - Палўанова, Г.Ж (SCIENCE and SOCIETY, 2022)
The article provides information on how to combat small rodents, the most common pests of agriculture, milk thistle - the rattlesnake and prevent large-scale economic damage. One of the main methods of struggle is the selection and application of a method that gives a concrete and clear entrance to the rescue of ten damaged objects from the rat by the method of harmless struggle.
Keywords: flat-toothed rat; plague; tularemia; pasteurellosis; ecological; mammalian rodents; mechanical; chemical methods